2011
DOI: 10.1073/pnas.1113061108
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA suggests the leading role played by men in the Neolithic dissemination

Abstract: The impact of the Neolithic dispersal on the western European populations is subject to continuing debate. To trace and date genetic lineages potentially brought during this transition and so understand the origin of the gene pool of current populations, we studied DNA extracted from human remains excavated in a Spanish funeral cave dating from the beginning of the fifth millennium B.C. Thanks to a "multimarkers" approach based on the analysis of mitochondrial and nuclear DNA (autosomes and Y-chromosome), we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 27 publications
5
95
0
Order By: Relevance
“…7,8 Two specimens were designated as members of haplogroup H, two were members of the U clade and three shared the 16223-16298-16327 HVS1 sequence motif characteristic of the root sequence of haplogroup C. 9,10 Specimen Ya34 carried a transition at 16357, characteristic of the C4a2 subbranch of the C clade. 10 While the majority of mtDNA lineages found in the Neolithic remains from the NPR can be ascribed to the haplogroups of West Eurasian origin and are in agreement with those previously reported for prehistoric haplogroups in West Eurasia, [11][12][13][14][15][16][17][18] our finding of East Eurasian lineages is uncommon in ancient European remains and has only been observed in the neighboring populations of the Carpathian Mountains. 19,20 Haplogroup C is a derivative of the M8 subclade of the Asianspecific M clade.…”
Section: Resultssupporting
confidence: 91%
“…7,8 Two specimens were designated as members of haplogroup H, two were members of the U clade and three shared the 16223-16298-16327 HVS1 sequence motif characteristic of the root sequence of haplogroup C. 9,10 Specimen Ya34 carried a transition at 16357, characteristic of the C4a2 subbranch of the C clade. 10 While the majority of mtDNA lineages found in the Neolithic remains from the NPR can be ascribed to the haplogroups of West Eurasian origin and are in agreement with those previously reported for prehistoric haplogroups in West Eurasia, [11][12][13][14][15][16][17][18] our finding of East Eurasian lineages is uncommon in ancient European remains and has only been observed in the neighboring populations of the Carpathian Mountains. 19,20 Haplogroup C is a derivative of the M8 subclade of the Asianspecific M clade.…”
Section: Resultssupporting
confidence: 91%
“…Taken together, these findings suggest that sub-haplogroups of G2a were frequent in Neolithic populations of the sixth-fourth millennia BC across Europe. Thus, if we take Y chromosomal haplogroup I2a (and possibly I1) as proxy for a Mesolithic paternal genetic substratum in Europe, we observe a similar pattern to the changeover in the mitochondrial DNA variability, in which NRY G lineages were predominant among Neolithic farmers across Europe and I lineages became rare [38,40,[43][44][45]49,51]. While the newly discovered NRY C haplogroup suggests additional Y lineages in eastern Hungary [41], the eastern Hungarian NRY data are still too few to estimate, whether there was paternal genetic difference between the populations of western and eastern Carpathian Basin.…”
Section: Discussionmentioning
confidence: 87%
“…Y chromosome study of modern-day Europeans has suggested a post-LGM expansion from a Franco-Cantabrian refugium for clade I1, and southeast European refugium for I2a1 based on high divergence time estimates [58]. I2a has indeed been found in Mesolithic and Neolithic Central and North European hunter-gatherers [33,34,40,41], as well as in Neolithic remains of southwestern Europe [44,45]. Haplogroup I2a (and possibly I1) might represent a pre-farming legacy of the NRY variation in Europe, alongside the recently described pre-Neolithic C (M130) haplogroups in Russia and Spain [35,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations